(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In the article, the researcher analyzes the art-pedagogical significance of teaching poetic dramas from a pedagogical perspective. In particular, in the study of stage speech techniques in the training of future actors, the technologies for developing artistic speech through the methods of scene-by-scene, scene-by-scene teaching of dramatic works written in poetic form, which are studied by students of the Institute of Culture and Arts, are discussed. From a pedagogical point of view, the specific features of teaching historical and modern poetic dramas are discussed. The complementary aspects and interdependence of stage speech and acting skills in the process of acting education at the Uzbek State Institute of Arts and Culture are analyzed in detail.